Efeitos da biocerâmica na recuperação muscular de diabéticos tipo 1 durante protocolo de exercícios resistidos - Lorenzetti, Lucielle Baumann (2018)
In type 1 diabetes mellitus chronic hyperglycemia state leads the organism to oxidative stress, and this is the main cause of complications resulting from the disease. For treatment, insulin therapy, proper diet and physical exercise are combined. In this study, the objective was to evaluate the bioceramic action associated to four weeks of a resistance physical exercise protocol in type 1 diabetics in variables of muscular performance and oxidative stress. Thirteen type 1 diabetic men initiated the study. They were randomly assigned to control group (GC) and bioceramic group (GB). Both performed the same four-week resistance exercise protocol, and the bioceramic group wore a T-shirt impregnated with bioceramic every night during the intervention period while the control group wore a placebo t-shirt. Anthropometric, neuromuscular performance and oxidative stress assessments were performed before and after intervention. Six participants finished the study. Anthropometric data showed slight post-intervention variations in both groups, GC n=3 and GB n=3, with an average increase in BMI. Hb1Ac had Δ% of 1.19 in GC and Δ% -2.41 in GB, with a reduction in the mean value of Hb1Ac in this group. Muscular performance evaluations demonstrated that both groups presented higher results after the intervention, with values of Δ% CMJ in GC 2.03 and Δ% CJM in GB 34,82; Δ% SJ in GC 7.11 and Δ% SJ in GB 21.10; Δ% 1RM squatting GC 11.73, and Δ% 1RM squatting GB 12.50; Δ% 1RM supine GC 11.17, and Δ% 1RM supine in GB 19,18. The oxidative stress evaluations had higher mean values of TBARS in the CG, with Δ% 129,67. GB had Δ% -1.48; carbonyl group had a reduction in mean values in both groups after the intervention. The SOD and CAT enzymes presented lower mean values after the intervention in the GC, with Δ% -45.77 for SOD and Δ% -27.93 for CAT. In GB, both enzymes had higher concentrations after the intervention, with Δ% of 65.44 for SOD and Δ% 43.11 for CAT. Muscular performance markers had a possible positive response to the proposed exercise protocol, with better Δ% results in GB. The main findings were related to oxidative stress, with reduction of mean values of TBARS, SOD and CAT in GB after the intervention. Individual variations were found in both groups. The study indicates a possible beneficial effect of using bioceramic t-shirts on markers of muscular performance and on oxidative stress.